THE REACTION PARAMETERS OF HEART RATE VARIABILITY FOR BIOFEEDBACK SESSIONS IN CLOSED LOOP OF PACED BREATHING IN PATIENTS WITH ARTERIAL HYPERTENSION ON THE BACKGROUND OF STANDARD DRUG THERAPY - E.A. Liuta; S.A.S. Belal; N.A. Vodyanitskaya; A.V. Martinenko; M.I. Yabluchansky (Bogomolets National Medical University, 2016)
Summery. We studied changes in parameters of heart rate variability (HRV) in sessions of biofeedback (BFB) in closed loop of paced breathing (PB) on the steps of the standard drug therapy in patients with arterial hypertension (AH). All 144 patients assessed the total power of the HRV, as well as very low frequency (VLF, ms2), low frequency (LF, ms2) and high-frequency domains (HF, ms2). Data were processed using parametric statistical techniques. It is proved that the addition of standard drug therapy biofeedback sessions in the loop of PB in patients with hypertension significantly increases the total power spectrum of HRV by increasing the capacity of VLF and HF out LF changes.